Determination of the natural mortality age of an holm oak ( Quercus ilex L.) stand in Corsica (Mediterranean Island) - Panaiotis, C; Carcaillet, C; M'Hamedi, M (Acta Oecologica, 1997)
Determination of old forest stand age and forestry history is problematic due to the difficulties which arise in obtaining core samples from trees. In the present paper, the natural mortality age and forestry history of a Corsican holm oak stand are estimated using the methods described below. Firstly, the correlation between stem age estimated from healthy stump counts in fellings and stem diameter is determined using a second order polynomial equation. Secondly, the distribution of stand diameter classes is analyzed by the BHATTACHARYA (1967) method. This method allows the identifica- tion of cohorts as well as the estimation of cohort mean diameters and theoretical tree count numbers. Using cohort mean diameters, we are able to estimate their age and discuss stand forestry history. Finally, the analysis of thirty broken stumps originating from senescent holm oak natural falls, is used to determine the mean natural mortality age of trees bused on their mean diameter. This natural mor- tality is estimated to occur at 170 -+ 46 years of age. The causes of holm oak mortality and the capacity of old stumps to renew the ecosystem are discussed in order to contribute to the conservation and man- agement of these woodland communities.
Keywords: Corsica; Dendrochronology; Forest structure; mediterranean forest; natural mortality; old forest; Quercus ilex